The Correlation Between Senior High School Students’ Personality Types and Writing Cerkak Ability - Yusuf Kholiq; Joko Sukoyo (AL-ISHLAH: Jurnal Pendidikan, 2023)
Students' personality types are thought to have a correlation with Cerkak's writing ability, and students with introverted personality types are thought to have better Cerkak's writing ability. This study aimed to determine the correlation between personality types and Cerkak's writing ability in class X students at a public senior high school in Gombong. This study used a correlational research design with a sample of 35 students. The sampling technique was carried out using the cluster random sampling technique. The data were collected through observation, interviews, and writing tests. Data writing tests analysis was performed by using regression and correlation. Data observation and interviews were performed by using qualitative descriptive. The results showed that personality type and the results of writing cerkak had a very strong correlation with a correlation coefficient of 0.874, and students with introverted personality types had better cerkak writing abilities than students with extroverted personality types. In this study, personality type has effect of 49.4% on the results of writing cerkak and the remaining 50.6% is influenced by factors not examined in this study. Hence, a correlation exists between personality type and cerkak writing ability in grade X students, with introverted children demonstrating superior writing skills compared to their extroverted counterparts.